Mockingjay [compact disc, unabridged] - Collins, Suzanne (Collins, Suzanne. Hunger Games (Series), 2010)
Having survived the Hunger Games twice before, Katniss Everdeen is lucky to be alive. However, she is far from safe. With the Capitol and President Snow blaming her for the strife plaguing District 12, Katniss must sacrifice herself to protect her loved ones.